Gastrointestinal Duplication Presenting as Neonatal Intestinal Obstruction: An Experience of 15 Years at Tertiary Care Centre - Kamal Nain Rattan; Shruti Bansal; Aastha Dhamija (EL-Med-Pub, 2016)
Background: Gastrointestinal tract (GIT) duplications are one of the rare congenital anomalies and can occur in any portion of the gastrointestinal tract but are more commonly encountered in small intestine. The duplication cysts cause symptoms like abdominal mass and intestinal obstruction requiring surgery or may remain asymptomatic. We are reporting our 15 years' experience duplication cysts presenting in neonates. Methods: It is a retrospective study undertaken in the department of pediatric surgery between 2001 and 2015 for GIT duplications in neonates. Patients were analyzed for their antenatal diagnosis, age, sex, clinical diagnosis, investigatory approach, operative management and surgical outcomes. Results: Total number of neonates, diagnosed with gastrointestinal duplication in the last 15 years, was 17. Male to female ratio was 3.3:1. The most common location was found to be the ileum occurring in 71% of cases. Apart from ileum, 2 cases of duodenal and 1 case each of gastric, colonic and cecal duplication cyst were encountered. Majority cases presented with sub-acute intestinal obstruction and were managed successfully by resection and end to end anastomosis. Associated gut atresia was found in 4 cases while 1 case was found to be associated with perforation of gut. Conclusion: Gastrointestinal tract duplications often present with typical symptoms of gastrointestinal tract obstruction. Early diagnosis and management is required to prevent postoperative morbidity and mortality.